Fitting a Round Peg into a Square Hole: Exploring Issues, Challenges, and Strategies for Solutions in Rural Home Care Settings - Beverly D Leipert; Marita Kloseck; Carol McWilliam; Dorothy Forbes; Anita Kothari; Abe Oudshoorn (Rural Nurse Organization; Binghamton University, 2007)
While home care has received much attention lately, little research to date has drawn on the experiences of rural multidisciplinary teams providing in-home care. Home care is typically studied in urban areas, with the tendency to expand urban practices to rural settings, often with problematic results. This paper presents findings regarding unique rural multidisciplinary home care issues, challenges, and strategies for solutions. Five focus group interviews were held with each of three rural multidisciplinary home care provider groups (n=19) in southwest Ontario, Canada. Findings revealed practice issues related to time, distance, communication, recruitment and retention, as well as system issues regarding poor understanding and scheduling of rural practice by administrators and urban employers. Study findings indicate that rural home care requires enhanced understanding and changes to policies and practices to provide efficient and effective care to rural residents. Best practice guidelines for home care in rural areas are urgently needed.